1991
DOI: 10.2337/diab.40.11.1410
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion and Aggregate Formation in Type I Diabetes Under Flow Conditions

Abstract: To study platelet activation as a phenomenon that may precede development of angiopathy in diabetes mellitus, we compared platelet adhesion and thrombus formation in a flow system with blood from insulin-dependent (type I) diabetic subjects with and without macroangiopathy and age- and sex-matched control subjects. Adhesion and thrombus formation on matrix of cultured human endothelial cells (ECM) and adhesion on matrix of human fibroblasts (FBM) were studied after exposure to flowing blood at shear rates of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To our knowledge, these studies were the first to evaluate firm platelet adhesion from diabetic patients under flow conditions to fibrinogen and vWF. A previous report on platelets adhesion under flow conditions to matrices formed by endothelial cells or fibroblasts showed no difference between the adhesion of platelets from diabetic patients and non-diabetic individuals [27]. At the same time, there are conflicting reports on platelet adhesion under flow conditions in vitro in animal models of diabetes.…”
Section: Evaluation Of Adhesion Potential Of Platelets From Diabetic Patientsmentioning
confidence: 93%
“…To our knowledge, these studies were the first to evaluate firm platelet adhesion from diabetic patients under flow conditions to fibrinogen and vWF. A previous report on platelets adhesion under flow conditions to matrices formed by endothelial cells or fibroblasts showed no difference between the adhesion of platelets from diabetic patients and non-diabetic individuals [27]. At the same time, there are conflicting reports on platelet adhesion under flow conditions in vitro in animal models of diabetes.…”
Section: Evaluation Of Adhesion Potential Of Platelets From Diabetic Patientsmentioning
confidence: 93%
“…Adherence of platelets from poorlycontrolled diabetic subjects to glass surfaces coated with glycated or unglycated collagen is not different from platelets from control subjects [14]. Also, ac-cumulation of platelets from diabetic subjects on extracellular matrix from control endothelial cells in vitro is similar to control platelets [15]. · In response to single injury to the aorta with a balloon catheter in vivo, the number of platelets which initially accumulates on the injured surface is similar in control and diabetic rats.…”
Section: Effect Of Diabetes On Platelet Accumulation and Turnover On mentioning
confidence: 99%
“…prostacyclin, ADPase, and NO, among others), anticoagulant substances (thrombomodulin and heparin-like substances, among others), and fibrinolysis stimulators (tissue plasminogen activator, or tPA) [57]. These functions are impaired in diabetes mellitus, and many studies have reported increased platelet activation in the plasma phase of coagulation, along with deficient fibrinolytic activity [8,29,54,[57][58][59]. These changes tend to favor a prothrombotic state in patients with diabetes, a situation that leads in turn to a higher risk of myocardial infarction, stroke, amputation, and vascular death [60].…”
Section: Altered Antithrombotic Functionmentioning
confidence: 99%
“…These changes lead to the prothrombotic state, which can favor the appearance of retinal ischemia [8,29,54,[57][58][59]. Therefore, one of the preventive measures that can be used for diabetic retinopathy is based on drugs that inhibit platelet activity while sparing or even enhancing endothelial antithrombotic function [8].…”
Section: Modulation Of the Antithrombotic Function Of The Endotheliummentioning
confidence: 99%